Monitoring the Evolution of ST Elevation Myocardial Infarction (STEMI) Complicated by Total Atrioventricular (AV) Block: A Case Study - Zuraida, Eli; Ningrat, Syahrul; Said, Syahrani (Poltekkes Kemenkes Gorontalo, 2024)
Background: Myocardial infarction is the necrosis of heart muscle due to a lack of oxygen, often caused by impaired blood flow in the coronary arteries. ST Elevation Myocardial Infarction (STEMI) is characterized by ST-segment elevation, increased cardiac enzymes, and chest pain. Inferior STEMI can lead to arrhythmic complications, such as Atrioventricular (AV) Block, which requires close Electrocardiographic (ECG) and hemodynamic monitoring by nurses. This case report focuses on the ECG evolution of posteroinferior STEMI progressing from sinus rhythm to Total AV Block.Purpose: To present the ECG monitoring of a STEMI patient with AV Block complications.Methods: A case study was conducted on a 47-year-old male who experienced chest pain with an onset of more than 48 hours, demonstrating ECG evolution from sinus rhythm with posteroinferior STEMI to Total AV Block.Results: The patient exhibited significant ECG changes from sinus rhythm with posteroinferior STEMI to total AV Block, necessitating several medical interventions for stabilization. Intensive monitoring and ongoing care were essential to support recovery.Conclusion: Patients with STEMI show characteristic ECG evolution. In inferior STEMI, Total AV Block can occur due to occlusion of coronary arteries, particularly the Right Coronary Artery (RCA). The nurse's role in managing complication risks and ECG monitoring is vital for rapid and effective intervention. Multidisciplinary collaboration is necessary to enhance patient care outcomes.